Nutritional Behavior and Medication Adherence among Patients Undergoing Hemodialysis - Maitham Abed Shawwat, Hussein Hadi Atiyah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Chronic kidney disease is a progressive disease with five phases based on the glomerular filtration rate. In each of these stages, the patient continues to suffer from the condition and must take responsibility for his health, such as changing his diet and lifestyle and taking significant doses of medication. If not treated effectively, Chronic kidney disease can lead to a high rate of morbidity and mortality, lowering the quality of life and hastening death. Objectives: This study aimed to evaluate the effectiveness of an interventional program on patients’ knowledge toward nutritional behavior and medication adherence as health-protective behaviors. Methodology: A quasi-experimental (tow-group pretest-posttest) design was used to conduct this study at the hemodialysis unit in Al-Hussain Teaching Hospital. A non-probability (purposive) sampling was used to select (80 patients) undergoing hemodialysis. To measure the effectiveness of the interventional program on patients’ knowledge, the researcher used a knowledge form which included (40) questions. The validity of the questionnaire and the interventional program were verified by presenting it to (17) experts. The reliability was determined using the test-retest approach for the knowledge questionnaire. Results: The study findings showed that there are highly statistically significant differences between the scores of patients knowledge in two levels of measurements (pre-test and post-test) at p-value (0.000), where the statistical mean of the overall knowledge at p-value of patients in the pre-test was (0.896), while it becomes (0.000) in post-test. Conclusion: The study concluded that the interventional program positively affects the patients’ knowledge concerning nutritional behaviors and medication adherence as health-protective behaviors.